The “Nusantara” Cash-Waqf Model: Designing Alternative Scheme for Infrastructure Financing - Raditya Hendra Pratama; Resi Ariyasa Qadri; Akhmad Khabibi (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2023)
The objective of this study is to design a cash waqf management framework for financing infrastructure in Indonesia's new capital, Nusantara. The scoping review methodology is used in this study to accomplish both research goals. The Publish or Perish application is used to collect scientific journal articles as part of the data collection process. A constructivist scoping review analysis procedure was used as the data analysis technique. The waqf program can be used to fund capital city infrastructure development projects, according to the study's findings. Our findings offer a cash waqf model that is linked to the mudharabah contract to pay for the state capital's relocation. The government can utilize this information as a springboard for developing financing regulations based on Islamic finance. By integrating pertinent stakeholders, further studies can employ the model created through the use of grounded theory. By conceiving of a cash Waqf system for funding the development of public infrastructure, our article advances Islamic finance literature.